Menghayati Asta Aiswarya Sebagai Kemahakuasaan Sang Hyang Widhi - Ni Putu Ayudya Putri; Nitya Yuli Pratistha (Pramana: Jurnal Hasil Penelitian, 2023)
Aiswarya is the form and nature of Ida Sang Hyang Widhi Wasa's omnipotence, both temporal and noetic, consisting of eight kinds of power, so that Aiswarya is also called Asta Aiswarya. Etymologically, asta aiswarya comes from the word "asta" which means eight and "aiswarya" which means omnipotence. So asta aiswarya are eight attributes of the omnipotence of Ida Sang Hyang Widhi Wasa (God Almighty). In the book Wrhaspatittatwa sloka 66 there is information about the attributes of God's omnipotence, including Anima, which means God is the smallest, Laghima which means the greatest, Prapti which means reaching all places, Isitwa which means beyond everything, Prakamya which means absolute will, Wasitwa which means powerful, and Yatrakamawasaitwa which means natural or unchangeable. Apart from the Wrhaspatittatwa teachings of Asta Aiswarya, they are also found in Bhagavadgita X.20, Rg. Weda X.90.1, Lontar Bhuana Kosa II.17, and Atharva Weda IV.16.2. This article will discuss the efforts to live up to the omnipotence of Ida Sang Hyang Widhi (God) as Asta Aiswarya